A STUDY ON BAY'TAWARRUQ (MONETIZATION) FROM THE PERSPECTIVE OF NATIONAL BANK MALAYSIA AND AAOIFI STANDARDS: MALAYSIAN PRACTICE - Abdurrahim, Muhammad Najib; Megat Laksana, Nan Noorhidayu; Abdul Aziz, Akhtarzaitie (2018)
(IFSA) on 2013, Islamic financial industry has shown its commitments towards the financial industry and its stakeholders through the development ofa distinctive products based on the various Sharr'ah contracts such as Islamic hire purchase for vehicle and machine based on the concept ofal-lidrah Thumma al-Bay' (a contract ofleasing ending with sale), islamic personal financing based on the concept ofBay' al-I'nah (sell and buy back with arrangement). Islamic house financing based on the concept of Mushdrakah Mutanaqi;ah (diminishing joint ventwes) and others. On 289 July 2005, the Shart'ah Advisory Council of National Bank Malaysia (SAC BNM) had resolved that financing and deposit product based on the concept oi Tu*a*rq is permissible. This resolution then has become an alternative way gr the Islamic financial institutions to overcome ttre tiquidity issue without relying on the controversial contract ofBay' al-'-Inah anymore. Tawarruq is a process where a person buys a commodity with deferred price, subsequently sells it on spot palanent, usually with lower price to another party other than the first seller, with intention to obtain cash/liquidity. Thus, this study aims to discuss the iole of National Bank Malaysia and Accounting and Auditing of Islamic Financial Institutions (AAOIFD Standard regarding the concept of Tawam.rq in Malaysia. With regard to the methodology, this study will use both qualitative and quantitative methods. ifo*"rr"r, the qualitative method will become the main method for this study. The instrument of qualitative method is an interview session with the main stakeholders involved in the development of Tawarruq Standard. This study will contribute from the theoretical and practical perspective of Tawamrq operation a:rd application in Malaysia, argument and deliberation ofTawarruq not only from classical lslamic perspective, but also from modern application and discussion.